Penerapan Metode SMART (Simple Multi Attribute Rating Technique) Pada Sistem Pendukung Keputusan Kelayakan Pemberian Kredit Pada Toko Utama Jaya Furniture - Djulianto, Teddy; Ratama, Niki (CV. Shofanah Media Berkah, 2023)
This rapid technological development has brought a new atmosphere to the business world or agency. At this time there is a transition in the method of granting credit which is done manually, into a decision by utilizing electronic technology, one of which is the use of a Decision Support System. Toko Utama Jaya furniture is a company engaged in the sale of furniture for household appliances such as tables, chairs, cabinets, beds and others. Toko Utama Jaya Furniture stands with a variety of services that offer various financing. In analyzing the credit granting process, the company forms a special division called Credit Analyst (CA). In the credit granting process, the methods used by credit analysts are still conventional and prone to abuse of authority. To prevent the risk of bad credit, companies must ensure the eligibility of prospective creditors before the credit agreement is approved. This process requires an analysis involving many assessment factors. credit in the economic sense is a delay in payment, namely money or goods received, now will be returned in the future along with the addition of a counterperformance. Based on the definition of credit, the customer is obliged to pay off his debt after a certain period of time with a predetermined amount of interest. The purpose of the research activities carried out is to design and build a web-based application, assess creditworthiness using the SMART method and conduct a search for alternative creditworthiness based on the weight of each predetermined criterion. The Simple Multi Attribute Rating Technique (SMART) method is a comprehensive decision-making model that takes into account qualitative and quantitative matters. Calculations in the SMART method are very simple so they do not require complicated mathematical calculations. Transparent The process of analyzing alternatives and criteria in SMART can be seen by the user so that the user can understand how the alternative was selected.